Does the Balance-Of-Payments Matter At the Regional Level? - Pedro N. Ramos (European Regional Science Association (ERSA), 2006)
The main focus of this paper is the importance of the balance-of-(international and interregional)-payments for the regional economies. Discussion centers on two points: 1) on one hand, we do believe that for regions, as a rule, at the overall balance-of-payments (BP) level, the size of imbalances is reduced; 2) on the other, we argue that even if relatively important imbalances arise their effect on regional economies is small. There are several reasons why regional BPs remain relatively well-balanced at overall level. The most important is that trade and current imbalances, that regions run very often with a considerable size, are easily financed by offsetting flows recorded as well in the BP. These trade and current imbalances, that do not pass into overall imbalances, are of benign kind. We present several reasons why that easy financing – allowing for trade and current imbalances – happens. As for the argument that a BP disequilibrium – if it arises – do not hit significantly a regional economy, that is the aftermath of a nationally integrated financial system, where the great majority of the regional units are only branches of national institutions operating all over the country. In this environment, a variation in the regional money stock (that is the counterpart of an overall BP imbalance) is not magnified by a money multiplier. We then conclude that as regions do not face any significant BP constraint, exports do not have any peculiar role in the regional growth process, and therefore the regional competitiveness debate is misplaced.
Keywords: 330